2015
DOI: 10.4049/jimmunol.1402603
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Delivery of IL-21 Overcomes Anti-Her2/Neu Resistance through Shifting Tumor-Associated Macrophages from M2 to M1 Phenotype

Abstract: Tumor resistance is a major hurdle to anti-Her2/neu Ab–based cancer therapy. Current strategies to overcome tumor resistance focus on tumor cell–intrinsic resistance. However, the extrinsic mechanisms, especially the tumor microenvironment, also play important roles in modulating the therapeutic response and resistance of the Ab. In this study, we demonstrate that tumor progression is highly associated with TAMs with immune-suppressive M2 phenotypes, and deletion of TAMs markedly enhanced the therapeutic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 52 publications
2
85
0
1
Order By: Relevance
“…The therapeutic effect of IL21 and anti-ErbB2 therapy may be attributed to the enhanced cytotoxicity of NK and CD8 þ T cells, enhanced antibody-dependent cellular cytotoxicity, or a decrease in number of Tregs. A recent study also suggested that the intratumoral delivery of IL21 in combination with anti-ErbB2 mAb therapy skews TAMs away from an inflammatory M2 phenotype (45). Taken together, our study supports a mechanism whereby anti-ErbB2 mAb therapy induces IL21 expression in CD4 þ T lymphocytes that binds to IL21R on CD8 þ T cells to drive an antitumor immune response against ErbB2 þ tumors.…”
Section: Discussionsupporting
confidence: 69%
“…The therapeutic effect of IL21 and anti-ErbB2 therapy may be attributed to the enhanced cytotoxicity of NK and CD8 þ T cells, enhanced antibody-dependent cellular cytotoxicity, or a decrease in number of Tregs. A recent study also suggested that the intratumoral delivery of IL21 in combination with anti-ErbB2 mAb therapy skews TAMs away from an inflammatory M2 phenotype (45). Taken together, our study supports a mechanism whereby anti-ErbB2 mAb therapy induces IL21 expression in CD4 þ T lymphocytes that binds to IL21R on CD8 þ T cells to drive an antitumor immune response against ErbB2 þ tumors.…”
Section: Discussionsupporting
confidence: 69%
“…Depletion of macrophages resulted in decreased efficacy of anti-CD142 mAb therapy in vivo, supporting that TAMs contributed to tumor cell elimination. In contrast, a recent study showed that removal of M2-like TAMs significantly stimulated both influx of CD8 þ cytotoxic T cells and tumor shrinkage after anti-HER2 mAb therapy in a HER2-dependent breast cancer model (30). In addition, local delivery of IL21 into the tumor environment skewed the M2 phenotype of TAMs into more classically activated cytotoxic M1 macrophages.…”
Section: Strategies To Enhance Adcpmentioning
confidence: 75%
“…Th17 cells are crucial for this antitumoral effect of cDC2 vaccination, but the exact downstream mechanisms still need elucidation. The Th17-associated cytokine IL-21 was reported to shift TAMs from M2-like to M1-like cells in breast tumours49, but effects of IL-17 on TAM polarization were not reported. Interestingly, GM-CSF was recently shown to regulate the M1-like phenotype of TAMs50 and is coming to the forefront as a Th17 signature cytokine5152.…”
Section: Discussionmentioning
confidence: 99%